'I Have Done Hundreds of Rock Paintings': On the Ongoing Rock Art Tradition among Samburu, Northern Kenya. Issue 2 (May 2021) - Goldhahn, Joakim; Labarakwe, Stephen Longoida; Skoglund, Peter; Westergren, Ebbe
Abstract : In this paper, we discuss observations from fieldwork in northern Kenya which revealed solid evidence for a vital ongoing rock art tradition among warriors of Samburu— lmurran . They make rock art during their lives as warriors, typically between the ages of 15 and 30, when they live away from their villages, herding cattle and thus representing a specific 'community of practice'. Our findings reveal that Samburu rock art is made predominantly as a leisure occupation, while camping in shelters, as part of activities also involving the preparation of food. Typical images include domestic animals, humans (both men and women) and occasionally wild animals such as elephants and rhinos. Each age-set and new generation of lmurran is inspired by previous artwork, but they also change the tradition slightly by adding new elements, such as the recent tradition of writing letters and names close to the images. We conclude that even though rock art as such is not part of any ritual or ceremonial setting, it plays an important role as an inter-generational visual culture that transfers a common ongoing cultural engendered warrior identity through time.